Introspice mare pectoris tui : Ascendenze neoplatoniche nella produzione dialogica di H.S. Skovoroda (1722-1794) - Maria Grazia Bartolini (Firenze University Press, 2010)
This book addresses certain aspects of the religious thought of H.S. Skovoroda (demonology, the struggle against sin, the spiritualisation of worldly time) against the background of Neoplatonism in its Judaic-Christian interpretation and the Byzantine mystic-ascetic tradition. The author proposes an analysis of Skovoroda's dialogues in which the search for Neoplatonist sources is combined with the identification of elements that can be traced to the tripartite breakdown of the spiritual progress of the Christian into praxis, gnosis. This division, typical of the Eastern Church, conceives spiritual life as an ascending path organised in progressive levels. The study of Skovoroda's universe-text yields two constants. The first is an intense interrelation between the Text and the divine Logos (the Biblical word), which, replicating the schema envisioned in the Christianisation of the cosmology of the Timeo, becomes an active architectural component of the same. The second is an image of the world dominated by a vertical/centripetal orientation, which implies the possibility of a return of things to God, the ultimate end of the path leading from the praxis to the theoria.
Keywords: Demonologia; Religioni; Skovoroda; Filosofia